2006
DOI: 10.1002/pd.1615
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound findings before amniocentesis in selecting the method of analysing the sample

Abstract: More than 95% of the aneuploidies can be detected if karyotyping is performed in addition to qf-PCR in about 15% of the cases selected on the basis of ultrasound findings before amniocentesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 15 publications
4
13
0
Order By: Relevance
“…Large-scale QF-PCR tests, performed in other diagnostic centres are basically in agreement with our investigations, thus confirming that although deliberately targeted to the analysis of selected disorders affecting three autosomes and the sex chromosomes, QF-PCR can detect the great majority of chromosome abnormalities in prenatal samples (Pertl et al, 1996(Pertl et al, , 1999aSchmidt et al, 2000;Levett et al, 2001;Bili et al, 2002;Mann et al, 2004;Brown et al, 2006;Ochshorn et al, 2006;Vrbicka et al, 2006;Kagan et al,2007).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Large-scale QF-PCR tests, performed in other diagnostic centres are basically in agreement with our investigations, thus confirming that although deliberately targeted to the analysis of selected disorders affecting three autosomes and the sex chromosomes, QF-PCR can detect the great majority of chromosome abnormalities in prenatal samples (Pertl et al, 1996(Pertl et al, , 1999aSchmidt et al, 2000;Levett et al, 2001;Bili et al, 2002;Mann et al, 2004;Brown et al, 2006;Ochshorn et al, 2006;Vrbicka et al, 2006;Kagan et al,2007).…”
Section: Discussionsupporting
confidence: 88%
“…In fetuses with abnormal ultrasound findings, the molecular assay detected 95% of all abnormalities diagnosed by cytogenetic analysis, clearly indicating that this is the particular risk category where it is possible to find chromosomal abnormalities that the molecular assay is not designed to detect (Cirigliano et al, 2005). These observations have recently been confirmed by retrospective analyses of large series of CVSs (Chitty et al, 2006) and amniotic fluids (Kagan et al, 2007) confirming fetal ultrasound as the main indication to decide if QF-PCR should be followed by a full fetal karyotype.…”
Section: Discussionmentioning
confidence: 86%
“…We have not accounted for this on our model, which focuses on DS. Prenatal diagnosis programmes may need to consider the use of invasive tests in pregnancies where the NIPT test is normal, but increased nuchal translucency or other structural abnormalities suggest other chromosomal rearrangements [39], [40]. This requires further evaluation when NIPT is used in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, failure to detect some of these aneuploidy cases should be weighed against the risk of miscarriage or the anxiety caused by copy number variants of unknown significance, poorly defined penetrance and/or variable expressivity [6]. Future directions might support the option of invasive prenatal diagnosis in cases where the NIPT was normal but the fetus has increased NT or structural abnormalities detected prenatally, as this is the group most likely to have other chromosomal rearrangements [49,50]. Chitty et al [51] reported that MLPA is able to detect 94.7%, compared to 68.4% by traditional karyotyping, of pathogenic rearrangements conferring a significant risk of adverse outcome.…”
Section: Discussionmentioning
confidence: 99%